Downregulation of miR-22 Contributes to Epithelial-Mesenchymal Transition in Osteosarcoma by Targeting Twist1 - Zhu, Shu-tao; Wang, Xiao; Wang, Jun-yi; Xi, Guang-hui; Liu, Yang (Frontiers in Oncology, 2020)
The epithelial-mesenchymal transition (EMT) is a vital step in osteosarcoma (OS) progression towards metastasis, but the specific molecular events governing this process are incompletely characterized, with miRNAs having increasingly been found to regulate the EMT. In this study, We assessed levels of miR-22 and its target, Twist1, via real-time PCR (qRT-PCR). We further used functional proliferation assays, measures of cell morphology, and western blotting to assess the functional relevance of miR-22 in OS, and confirmed Twist1 as a miR-22 target via luciferase reporter assay. We observed a significant decrease in miR-22 levels in OS tumor samples relative to normal tissue, with such downregulating being significantly associated with tumor histological grade. When overexpressed, miR-22 impaired OS cell proliferation and EMT progression. We found Twist1 to be a direct miR-22 target, with levels of miR-22 and Twist1 mRNA being inversely correlated in patient samples. When overexpressed, miR-22 suppressed Twist1 translation and thereby attenuated the EMT in OS cells. These results clearly demonstrate that miR-22 can regulate the EMT in OS cells via targeting Twist1, thus highlighting a potentially novel pathway that can be therapeutically targeted in order to treat OS.